Nutrition and diet therapy principles and practice - Cataldo, Corinne Balog (West/Wadsworth, 1999)
Organized by diets rather than organ systems or disease states, this text includes margin definitions, key points, self-check quizzes, self-studies, case studies and question-and-answer style "Nutrition in Practices".